Perilaku Seks Bebas di Tinjau Dari Faktor yang Mempengaruhi di SMA Negeri 1 Wawonii Kab. Konawe Kepulauan - Resky, Fauzan; Ahri, Reza Aril; Ikhtiar, Muhammad (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Free sex or sexual conduct premarital teen at the age of 15-24 years in Indonesia tends to rise because it's optimal yet prosperous family education and low levels of education and understanding of the youth against the risk of sex outside of marriage. This research was conducted aiming to review and analyze in-depth information regarding the behavior of free sex. The type of research used a qualitative approach method i.e. phenomenology through in-depth interview, observation and documentation as long as the research progresses. The results of this study indicate that the role of the media and the knowledge is highly influential on the behavior of adolescents in Wowoni Island Islands particularly in SMA Negeri 1 Wawonii, Regency Wowoni Island Islands that This can change the occurrence of changes in teenage lifestyles in this style look, the Association's daily entertainment, and manners. considered to follow the development of the times. This shows the incidence of teenage desire free sex conduct is caused by the presence of sexual stimulation, watch porn videos, pictures, often the same tandem pairs thus leading sexually stimulation, imagine the sex scenes, where imagination that appears is the result of the accumulation of the teen experience for interacting with the surrounding environment. The presence of sexual stimulation which then push the teens to perform sex free. This research is expected of the students do not perform free sex behaviors to avoid disease risk such as sexually transmitted diseases and reproductive health are maintained.